Up in the air with VR360 - Santano, Delas *; Zi, Siang See; Chi, How Fong; Thwaites, Harold * (Intellect, 2018)
Both drones and 360-degree video (VR 360) have been attractive topics for the past decade. 360-degree videos hit Internet fame as soon as YouTube and Facebook started to adopt them into their ecosystem, which made users familiar with and intrigued by these techniques. This definitely made the camera industry race to democratize 360-degree cameras, and now we are graced with affordable, out-of-the-box 360 cameras from Samsung, Ricoh, and Garmin, to Nikon. The company DJI has been the leading drone manufacturer since their first quadcopter captivated our imagination and love of playing with remote control toys in our young age. With this same adventurous and imaginative mindset, we embarked on combining the two technologies: 360-degree cameras and aerial drones. In this article we present the development of an approach to an aerial virtual reality 360 video capture technique. We retrofitted a drone with a 360 spherical panorama camera for acquiring source aerial visual content. Our case study, as described in this article, reproduces an experiment using a 360-fly-by video for the intended use of an event launching in which user perception was being observed in terms of practicality and suitability. A user study was conducted to gauge the usability of comparing aerial VR360 being experienced on hand-held multimedia tablets and head-mount-devices (HMD). We also describe the proposed configuration and workflow of aerial 360-video and identify its potential capabilities and limitations, a user evaluation study and directions for future work. In the discussion section, we share how this setup can affect the decisions of the producer, director or the director photography in achieving the creative shot that they aim to produce.